Resilience Evaluation and Enhancement Strategy of Distribution Network Considering Impact of Seismic Attack on Transportation Networks - YAN Wenting, YANG Long, LI Changcheng, LUO Wei (Shanghai Jiaotong Daxue xuebao, 2023)
Serious earthquake disasters not only cause power outages in distribution network, but also destroy transportation networks, which hinders the transportation of resources for restoration of distribution network and slows down the restoration. This paper proposes an improved resilience evaluation method and a resilience enhancement strategy of distribution network considering the effects of seismic attack on transportation networks. First, a seismic attack model is established to describe the relation between earthquake disasters and failure probability of transportation-distribution networks based on peak ground acceleration. The impact of earthquake disasters on transportation-distribution networks is quantified, and the failure scenarios are generated. Then, a resilience evaluation index is proposed by introducing the waiting time for road repair of emergency repair teams. Afterwards, a bi-level optimization model for distribution network restoration considering the fault line repair, the road repair, and the emergency resource scheduling is established and solved. The upper layer aims at the minimum power loss load, while the lower layer takes the minimum waiting time of the repair team as the goal. Finally, case studies on a coupling example of a 12-node transportation network and an IEEE 33-node distribution network verify the feasibility of the improved resilience index and the effectiveness of the proposed method. The results show that the resilience index considering seismic attack on transportation networks is accurate, and the restoration strategy can effectively enhance the resilience of distribution network in earthquake disasters.